Analisis Penerapan Tax Planning PPh Pasal 21 Berdasarkan UU Harmonisasi Peraturan Perpajakan sebagai Upaya Optimalisasi Penghematan Beban PPh Badan : Studi Kasus PT. ABC - Muhammad Reza Setiady; Deliza Henny (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to answer questions regarding: 1) Application of the calculation of Income Tax Article 21 for Permanent Employees based on the PT HPP Law. ABC, 2) Comparison of the calculation of Income Tax Article 21 using the Net, Gross and Gross Up methods for permanent employees of PT. ABC, 3) Efforts to be made if in calculating PPh Article 21 for permanent employees there is a tax charge above the Corporate Income Tax rate, and 4) How to determine the method for calculating PPh Article 21 tax for permanent employees in an effort to optimize the corporate income tax burden. The data collection techniques used include documentation, where this research was carried out by collecting data through other parties, namely Partnership Suryani Suyanto & Associates. Then the data was processed by the author to produce the following data: 1) PT. ABC in calculating Income Tax Article 21 for permanent employees in 2022 uses the Net Method, where the company bears the tax costs that must be incurred. 2) Calculations using the Net, Gross and Gross Up methods have their respective advantages and disadvantages, but it is better to use the Gross method Up for employees whose income is below Rp. 500,000,000, where the company provides tax benefits which can later be charged in the company's profit and loss report. 3) the efforts made by the company if in calculating PPh Article 21 there are two methods used in one company, 4) The appropriate method for PT. In order to streamline the taxes that must be paid, ABC uses the Net method for employees whose income is above Rp. 500,000,000 and the Gross Up method for employees whose income is below Rp. 500,000,000. When using these 2 (two) methods PT. ABC will save taxes, and this method can be applied for next year's tax planning.